ANALYZING THE FACTORS INFLUENCING EMPLOYEE RETENTION AT PT. BANK NEGARA INDONESIA (BNI) PERSERO - Warouw, Angela Alvina; Lapian, S. L.H.V.J. (FEB Universitas Sam Ratulangi Manado, 2015)
Employee retention issues are emerging as the most critical workforce management challenges. The dynamics of the work environment have to reflect a diverse population comprised of individuals whose motivations, beliefs and value structures differ vastly from the past and from one another. Bank Negara Indonesia (BNI) would want to adopt particular strategies that contribute to the retention of their most valued employees in one while avoiding control methods that would appeal the employees in the other. Research objectives are to analyze the factors influencing Employee Retention for employees in PT. BNI 46 Persero. Theories supporting this research are human resource management and employee retention. The population observed are employees of BNI with sample as many as 100 respondents. Result and conclusions are from all variables of the factors influencing employee retention (career development, remuneration/compensation, positive recognition staff engagement and management), remuneration/compensation, staff engagement and management are the most influencing variables. Keywords: organizational factor, employee retention